Comparison of prediction methods for road traffic noise - CZABALAY, L.; SÁRVÁRI, L. (Archives of Acoustics, 1985)
The Sanitary-Epidemiological Station of County Gyor-Sopron has accomplished some analysis of road traffic noise. On the basis of these investigations an answer should be given to the question of how far prediction methods for road traffic noise are reliable and to what extent they can be used for planning. The investigations will take 2 years (1984-1985). Research work was sponsored by the National Authority for Environment Protection and Nature Conservation. This report outlines the investigations performed in 1984, and the data published therein may be modified as required according to the 1985 investigations.